Radiopharmaceuticals and Fluorescein Sodium Mediated Triple‐Modality Molecular Imaging Allows Precise Image‐Guided Tumor Surgery. Issue 13 (24th April 2019) - Zheng, Sheng; Zhang, Zeyu; Qu, Yawei; Zhang, Xiaojun; Guo, Hongbo; Shi, Xiaojing; Cai, Meishan; Cao, Caiguang; Hu, Zhenhua; Liu, Haifeng; Tian, Jie
Abstract: Radical resection is the most effective method for malignant tumor treatments. However, conventional imaging cannot fully satisfy the clinical needs of surgical navigation. This study presents a novel triple‐modality positron emission tomography (PET)–Cerenkov radiation energy transfer (CRET)–confocal laser endomicroscopy (CLE) imaging strategy for intraoperative tumor imaging and surgical navigation. Using clinical radiopharmaceuticals and fluorescein sodium (FS), this strategy can accurately detect the tumor and guide the tumor surgery. The FS emission property under Cerenkov radiation excitation is investigated using 2‐deoxy‐2‐ 18 F‐fluoroglucose and 11 C‐choline. Performances of the PET–CRET–CLE imaging and the CRET–CLE image‐guided surgery are evaluated on mouse models. The CRET signal at 8 mm depth is stronger than the Cerenkov luminescence at 1 mm depth in phantoms. In vivo experiments indicate that 0.5 mL kg −1 of 10% FS generates the strongest CRET signal, which can be observed immediately after FS injection. A surgical navigation study shows that the tumors are precisely detected and resected using intraoperative CRET–CLE. In summary, a PET–CRET–CLE triple‐modality imaging strategy is developed. This strategy can detect the tumors and precisely guide the tumor resection using clinical pharmaceuticals. This triple‐modality imaging shows high potential in surgical navigation research and clinical translation. Abstract : A triple‐modality imaging strategy is developed for intraoperative tumor imaging and surgical navigation. In this strategy, clinical radiopharmaceuticals and FDA approved fluorescein are applied to imaging the tumor from various scales. In vivo experiments demonstrate that the triple‐modality imaging strategy can precisely guide the tumor resection, which shows high potential for clinical translation.